Laminated ceramic capacitor and method of manufacturing laminated ceramic capacitor
The multilayer ceramic capacitor design with controlled sintering aid segregation addresses capacitance loss and densification issues, achieving enhanced performance through optimized electrode structure and sintering aid distribution.
Patent Information
- Application Number
- JP2023107446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
The addition of a sintering aid in multilayer ceramic capacitors leads to a decrease in capacitance due to its lower dielectric constant, while insufficient sintering at low temperatures results in inadequate densification of the ceramic layer.
A multilayer ceramic capacitor design with segregated portions containing sintering aid elements in non-electrode areas, where the ratio of these segregated areas to the total electrode area is limited to 35% or less, ensuring high capacitance and effective sintering without excessive dielectric constant reduction.
The solution maintains high capacitance and improves the lifespan of the capacitor by reducing the concentration of sintering aid in dielectric regions and promoting denser crystal grain formation, thereby alleviating electric field concentration.
Smart Images

Figure 2025006567000001_ABST
Abstract
Description
[Technical field]
[0001] The disclosure of the present specification mainly relates to a multilayer ceramic capacitor and a method for manufacturing the multilayer ceramic capacitor. The disclosure of the present specification also relates to a circuit module including the multilayer ceramic capacitor and an electronic device including the circuit module. [Background technology]
[0002] Multilayer ceramic capacitors are used in various electronic devices. Multilayer ceramic capacitors are produced by stacking laminate units, each having an internal electrode pattern formed on the surface of a ceramic green sheet containing ceramic powder, to form a green laminate, and then firing the green laminate. It is known that adding a sintering aid to the ceramic green sheet can promote sintering of the ceramic powder by firing at a low temperature. Known examples of sintering aids include Si (silicon), which becomes liquid during firing. A conventional multilayer ceramic capacitor produced using ceramic green sheets to which a sintering aid has been added is described in JP 2009-084111 A. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-084111 A Summary of the Invention [Problem to be solved by the invention]
[0004] Since the sintering aid has a lower dielectric constant than the main phase oxide (e.g., barium titanate) of the ceramic green sheet, the capacitance of the multilayer ceramic capacitor decreases when the amount of the sintering aid is increased. On the other hand, when the amount of the sintering aid is small, the ceramic layer does not become sufficiently dense when the green laminate is sintered at a low temperature.
[0005] It is an object of the invention disclosed in this specification to solve or alleviate at least some of the above-mentioned problems. A more specific object of the invention disclosed in this specification is to provide a multilayer ceramic capacitor in which a decrease in capacitance due to a sintering aid is suppressed.
[0006] Objects of the present invention other than those mentioned above will become clear throughout the entire description of the specification. The invention disclosed in this specification may solve problems that are understood from other than the description in the "Problems to be Solved by the Invention" column. When the effects of an embodiment are described in this specification, the problems of the invention corresponding to the embodiment can be understood from the effects. [Means for solving the problem]
[0007] Various inventions disclosed in this specification may be simply referred to as "the present invention". A multilayer ceramic capacitor in one aspect of the present invention includes a body having a first internal electrode layer, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer. The ceramic layer is formed from a ceramic material to which a sintering aid containing a sintering aid element as a main component is added. A first external electrode is provided on the body so as to be electrically connected to the first internal electrode layer. Also, a second external electrode is provided on the body so as to be electrically connected to the second internal electrode layer. The first internal electrode layer has a first electrode portion which is a sintered body of a main component metal element, and a first non-electrode portion surrounded by the first electrode portion. The second internal electrode layer has a second electrode portion which is a sintered body of a main component metal element, and a second non-electrode portion surrounded by the second electrode portion. The first non-electrode portion and the second non-electrode portion each have a segregation portion containing a sintering aid element. The ratio of a second area representing the area of the segregation portion to a first area representing the sum of the areas of the first internal electrode layers and the second internal electrode layers in a cross section of the body cut along the lamination direction is 35% or less. Effect of the Invention
[0008] According to one embodiment of the invention disclosed in this specification, it is possible to provide a multilayer ceramic capacitor in which a decrease in capacitance caused by a sintering additive is suppressed. [Brief description of the drawings]
[0009] [Figure 1] 1 is a perspective view showing a schematic diagram of a multilayer ceramic capacitor according to an embodiment of the present invention; [Diagram 2] 2 is a cross-sectional view that illustrates a schematic cross section of the capacitor of FIG. 1 taken along line II. [Diagram 3] 3 is an enlarged cross-sectional view showing a part (area A) of the cross section of FIG. 2 in an enlarged manner. [Figure 4] 3 is an enlarged cross-sectional view showing a part (region B) of the cross section of FIG. 2 in an enlarged manner. [Diagram 5] FIG. 2 is a flow chart showing the flow of a method for manufacturing a multilayer ceramic capacitor according to an embodiment of the present invention. [Figure 6a] 1A to 1C are schematic diagrams illustrating a process for producing a multilayer ceramic capacitor. [Figure 6b] 1A to 1C are schematic diagrams illustrating a process for producing a multilayer ceramic capacitor. [Figure 7] 1 is a cross-sectional view that typically shows a cross section of a conventional multilayer ceramic capacitor in which a ceramic layer intrudes into a non-electrode portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Various embodiments of the present invention will be described below with reference to the drawings as appropriate. Components common to multiple drawings are given the same or similar reference symbols throughout the multiple drawings. Please note that the drawings are not necessarily drawn to scale for the sake of convenience. The embodiments described below do not necessarily limit the invention according to the claims. Elements described in the following embodiments are not necessarily essential to the solution of the invention.
[0011] For ease of explanation, each drawing may include an L axis, a W axis, and a T axis that are perpendicular to each other. In this specification, the dimensions, arrangement, shape, and other features of each component of the multilayer ceramic capacitor 1 may be explained based on the L axis, the W axis, and the T axis.
[0012] 1 Multilayer ceramic capacitor 1 1-1 Basic structure of multilayer ceramic capacitor 1 The basic structure of the multilayer ceramic capacitor 1 in accordance with the first embodiment will be described with reference to Fig. 1 and Fig. 2. Fig. 1 is a perspective view of the multilayer ceramic capacitor 1 in accordance with the first embodiment. Fig. 2 is a cross-sectional view that typically shows a cross section of the multilayer ceramic capacitor 1 taken along line II.
[0013] The multilayer ceramic capacitor 1 includes a main body 10, and a first external electrode 31 and a second external electrode 32 provided on the main body 10. The first external electrode 31 is disposed spaced apart from the second external electrode 32. In the example shown in Fig. 2, the first external electrode 31 is disposed spaced apart from the second external electrode 32 in the L-axis direction.
[0014] The main body 10 includes a plurality of ceramic layers 11, a plurality of first internal electrode layers 21, and a plurality of second internal electrode layers 22. The ceramic layer 11 is disposed between the first internal electrode layer 21 and the second internal electrode layer 22 adjacent to the first internal electrode layer 21. In this specification, when it is not necessary to distinguish the first internal electrode layer 21 and the second internal electrode layer 22 from each other, the first internal electrode layer 21 and the second internal electrode layer 22 may be collectively referred to as "internal electrode layers".
[0015] The main body 10 has an upper surface 10a, a lower surface 10b, a first end surface 10c, a second end surface 10d, a first side surface 10e, and a second side surface 10f. The outer surface of the main body 10 is defined by the upper surface 10a, the lower surface 10b, the first end surface 10c, the second end surface 10d, the first side surface 10e, and the second side surface 10f.
[0016] The upper surface 10a and the lower surface 10b form the surfaces at both ends of the main body 10 in the height direction (T-axis direction). In other words, the upper surface 10a and the lower surface 10b face each other in the T-axis direction. The first end surface 10c and the second end surface 10d form the surfaces at both ends of the main body 10 in the length direction (L-axis direction). In other words, the first end surface 10c and the second end surface 10d face each other in the L-axis direction. The first side surface 10e and the second side surface 10f form the surfaces at both ends of the main body 10 in the width direction (W-axis direction). In other words, the first side surface 10e and the second side surface 10f face each other in the W-axis direction. The upper surface 10a and the lower surface 10b are spaced apart by the height dimension of the main body 10, the first end surface 10c and the second end surface 10d are spaced apart by the length dimension of the main body 10, and the first side surface 10e and the second side surface 10f are spaced apart by the width dimension of the main body 10.
[0017] The main body 10 is constructed by stacking the ceramic layers 11, the first internal electrode layers 21, and the second internal electrode layers 22 along a stacking direction. In the illustrated embodiment, the ceramic layers 11, the first internal electrode layers 21, and the second internal electrode layers 22 are stacked along the T-axis direction. The stacking direction may be along the T-axis as illustrated, or along the L-axis or W-axis. The ceramic layers 11 arranged at both ends in the stacking direction may be called cover layers.
[0018] In the illustrated embodiment, the main body 10 is constructed by stacking the ceramic layers 11, the first internal electrode layers 21, and the second internal electrode layers 22 along the T-axis direction. For this reason, the T-axis direction may be referred to as the stacking direction. An upper cover layer may be provided on the upper surface of this stack. A lower cover layer may be provided on the lower surface of this stack. The upper cover layer and the lower cover layer may be made of the same material as the ceramic layers 11. The upper cover layer and the lower cover layer may be part of the main body 10.
[0019] One end of the first internal electrode layer 21 is drawn toward the outside of the main body 10. The first internal electrode layer 21 is connected to a first external electrode 31 provided on the surface of the main body 10. One end of the second internal electrode layer 22 is drawn toward the outside of the main body 10. The second internal electrode layer 22 is connected to a second external electrode 32 provided on the surface of the main body 10. In the illustrated embodiment, the first internal electrode layer 21 is drawn toward the outside of the main body 10 from one end in the L-axis direction. The first internal electrode layer 21 is connected to the first external electrode 31 at one end in the L-axis direction of the main body 10. The second internal electrode layer 22 is drawn toward the outside of the main body 10 from the other end in the L-axis direction. The second internal electrode layer 22 is connected to the second external electrode 32 at the other end in the L-axis direction of the main body 10. 2, the first internal electrode layer 21 and the second internal electrode layer 22 are respectively drawn out to the opposing first end surface 10c and second end surface 10d, but the first internal electrode layer 21 and the second internal electrode layer 22 may be drawn out from various surfaces of the main body 10 depending on the arrangement and shape of the first external electrode 31 and the second external electrode 32. For example, when the first external electrode 31 and the second external electrode 32 are both arranged on the lower surface 10b, the first external electrode 31 and the second external electrode 32 are both drawn out from the lower surface. The first external electrode 31 and the second external electrode 32 may be provided on any surface of the main body 10 as long as they are spaced apart from each other.
[0020] When a voltage is applied between the first external electrode 31 and the second external electrode 32 , a capacitance is generated between the first internal electrode layer 21 and the second internal electrode layer 22 .
[0021] 2, for the sake of simplicity, five layers each of the first internal electrode layers 21 and the second internal electrode layers 22 are shown, but the multilayer ceramic capacitor 1 can have any number of laminations. For example, the multilayer ceramic capacitor 1 can have 300 to 1000 layers of the first internal electrode layers 21 and the second internal electrode layers 22. In other words, the number of laminations in the multilayer ceramic capacitor 1 can be 300 to 1000 layers.
[0022] The multilayer ceramic capacitor 1 can be mounted on an electronic circuit board (not shown). The electronic circuit board on which the multilayer ceramic capacitor 1 is mounted is sometimes called a circuit module. Various electronic components other than the multilayer ceramic capacitor 1 can also be mounted on the circuit module. This circuit module can be mounted in various electronic devices. Electronic devices in which the circuit module can be mounted include smartphones, tablets, game consoles, automotive electrical equipment, servers, and various other electronic devices.
[0023] In one embodiment, the main body 10 may be configured to have a rectangular parallelepiped shape. In this specification, the term "rectangular parallelepiped" or "rectangular parallelepiped shape" does not mean only a "rectangular parallelepiped" in the strict mathematical sense. As described below, the corners and / or sides of the main body 10 may be curved. The dimensions and shapes of the main body 10 are not limited to those explicitly described in this specification.
[0024] In one embodiment, the dimension (length dimension) of the multilayer ceramic capacitor 1 in the L-axis direction is in the range of 0.2 mm to 2.5 mm, the dimension (width dimension) in the W-axis direction is in the range of 0.1 mm to 3.5 mm, and the dimension (height dimension) in the T-axis direction is in the range of 0.1 mm to 3.0 mm. In one embodiment, the length dimension of the multilayer ceramic capacitor 1 may be greater than the width dimension. In one embodiment, the height dimension of the multilayer ceramic capacitor 1 may be greater than the width dimension. In one embodiment, the width dimension of the multilayer ceramic capacitor 1 may be greater than the length dimension.
[0025] 1-2 First internal electrode layer 21 and second internal electrode layer 22 1-2-1 Composition of the first internal electrode layer 21 and the second internal electrode layer 22 In one embodiment, the first internal electrode layer 21 contains a base metal such as Ni (nickel), Cu (copper), or Sn (tin) as a main component. Based on the total mass of the first internal electrode layer 21, a component contained in the first internal electrode layer 21 at 50 wt% or more can be the main component of the first internal electrode layer 21. The first internal electrode layer 21 desirably contains 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more of the base metal as the main component.
[0026] The first internal electrode layer 21 may contain an auxiliary element in addition to the main component metal element. The first internal electrode layer 21 is an element that easily forms a compound with a sintering aid element contained in a sintering aid (described later) added to the raw material of the ceramic layer 11. The auxiliary element that may be contained in the first internal electrode layer 21 is, for example, one element or two or more elements selected from the group consisting of Al (aluminum), Zn (zinc), B (boron), and Si (silicon).
[0027] In one embodiment, the internal electrode layer may contain 0.01 at% or more and 5 at% or less of sub-elements with respect to 100 at% of the main component metal element. When the internal electrode layer contains two or more elements as sub-elements, the total concentration of the two or more sub-elements is 0.01 at% or more and 5 at% or less.
[0028] The explanation regarding the components of the first internal electrode layers 21 also applies to the components of the second internal electrode layers 22.
[0029] In one embodiment, the film thickness (dimension in the T-axis direction) of the first internal electrode layer 21 is 0.1 μm or more and 2 μm or less. In one embodiment, the film thickness of the first internal electrode layer 21 is desirably 0.4 μm or less. The explanation regarding the film thickness of the first internal electrode layer 21 also applies to the second internal electrode layer 22.
[0030] 1-2-2 Electrode and non-electrode parts The internal electrode layer will be further described with reference to FIG. 3. FIG. 3 is an enlarged cross-sectional view showing an area A of the cross section of the main body 10 shown in FIG. 2. Area A is an area with a dimension L0 in the L-axis direction of about 50 μm. As shown in FIG. 3, the first internal electrode layer 21 includes a first electrode portion 21a containing a main component metal element and a first non-electrode portion 21b surrounded between the first electrode portions 21a. The first internal electrode layer 21 can include a plurality of first non-electrode portions 21b. The first electrode portion 21a includes a sintered body of a main component metal element. Therefore, the first electrode portion 21a has high conductivity. As shown in FIG. 3, the first electrode portion 21a of the first internal electrode layer 21 is observed to be arranged in a plurality of parts separated by the first non-electrode portion 21b in a cross section cut along the stacking direction (the T-axis direction in FIG. 3).
[0031] The first non-electrode portion 21b is interposed between the first electrode portions 21a adjacent to each other in the L-axis direction, and has higher insulation than the first electrode portions 21a. Conventional multilayer ceramic capacitors also include highly insulating regions in the internal electrode layers. Most of the highly insulating regions in the internal electrodes of conventional multilayer ceramic capacitors are occupied by a part of the ceramic layer and / or voids. In contrast, the first non-electrode portion 21b in the present invention includes a secondary phase formed by solidifying a liquid phase sintering aid that has flowed between the first electrode portions 21a during the manufacturing process of the multilayer ceramic capacitor 1, as described later. Thus, the first non-electrode portion 21b contains a sintering aid element contained in the sintering aid. A part of the first non-electrode portion 21b may be occupied by an oxide of a subelement, a part of the ceramic layer 11, and / or voids.
[0032] As will be described in detail later, the first internal electrode layer 21 is formed by firing an internal electrode pattern including a main component metal element. As the sintering of the main component metal element progresses in this firing process, the shape of the sintered body of the main component metal element approaches a spherical shape. In the firing process, the sintered body of the main component metal element becomes spherical, so that voids are generated between adjacent sintered bodies of the main component metal element. In a conventional multilayer ceramic capacitor, as sintering of the ceramic layer progresses after voids are generated between the sintered bodies of the main component metal element, a part of the sintered ceramic layer enters the voids (voids) between the sintered bodies of the main component metal element. For this reason, in a conventional multilayer ceramic capacitor, a highly insulating region is included between the sintered bodies of the main component metal element in the internal electrode layer, and most of this highly insulating region is occupied by a part of the ceramic layer and / or voids. In contrast, in the multilayer ceramic capacitor 1 described in this specification, during the firing process in production, the softened liquid phase sintering aid can penetrate into the voids formed between the sintered compacts of the main component metal elements before the sintered ceramic layers penetrate into the voids between the sintered compacts of the main component metal elements.
[0033] In one embodiment, the continuity rate of the internal electrode layer in the multilayer ceramic capacitor 1 is preferably 75% or more. The continuity rate is preferably 80% or more, and more preferably 90% or more. The continuity rate of the first internal electrode layer 21 can be calculated as follows. First, the multilayer ceramic capacitor 1 is polished so that the LT surface becomes the observation surface. Next, a region A included in this observation surface is observed with a SEM (scanning electron microscope), and a region that appears bright in the SEM image due to a contrast difference is specified as the first electrode portion 21a. Then, the length of this first electrode portion 21a (in the illustrated example, the length along the L-axis direction) is measured, and the side lengths L1, L2, ..., Ln are summed up. The value obtained by dividing the sum of the lengths of the first electrode portions 21a in this region A by the length L0 of the measurement region (i.e., (L1 + L2 + ... Ln) / L0) can be defined as the continuity rate of one first internal electrode layer 21. The main body 10 includes first internal electrode layers 21, and the continuity rate can vary depending on which layer is focused on among the plurality of first internal electrode layers 21. Therefore, ten different first internal electrode layers 21 are selected, and the average of the continuity rates calculated for each of the selected first internal electrode layers 21 can be defined as the continuity rate of the first internal electrode layers 21 in the multilayer ceramic capacitor 1.
[0034] Like the first internal electrode layer 21, the second internal electrode layer 22 can also include an electrode portion containing a main component metal element and a non-electrode portion surrounded by the electrode portion. Specifically, as shown in FIG. 3, the second internal electrode layer 22 includes a second electrode portion 22a containing a main component metal element and a second non-electrode portion 22b surrounded by the second electrode portion 22a. The second internal electrode layer 22 can include a plurality of second non-electrode portions 22b. The first non-electrode portion 21b may include a secondary phase formed by solidifying a liquid phase sintering aid that has flowed between the first electrode portions 21a during the manufacturing process of the multilayer ceramic capacitor 1. The continuity rate of the second internal electrode layer 22 is defined in the same manner as the continuity rate of the first internal electrode layer 21. The average of the continuity rate of the first internal electrode layer 21 and the continuity rate of the second internal electrode layer 22 can be defined as the continuity rate of the internal electrode layer in the multilayer ceramic capacitor 1.
[0035] In the multilayer ceramic capacitor 1, a capacitance is generated in a region where the first electrode portion 21a of the first internal electrode layer 21 and the second electrode portion 22a of the second internal electrode layer 22 face each other in the lamination direction, i.e., in the T-axis direction in the illustrated embodiment. Conversely, the first non-electrode portion 21b and the second non-electrode portion 22b do not generate a capacitance. Therefore, in order to make the multilayer ceramic capacitor 1 have a high capacity, it is desirable that the continuity rate of the internal electrode layers is high. In one aspect, the continuity rate of the internal electrode layers is 75% or more. The continuity rate of the internal electrode layers is desirably 80% or more, and more desirably 90% or more. By increasing the continuity rate of the internal electrode layers, the capacitance of the multilayer ceramic capacitor 1 can be improved.
[0036] The first non-electrode portion 21b is interposed between the first electrode portions 21a that generate capacitance in the multilayer ceramic capacitor 1 in the length direction of the cross section of the internal electrode layer, i.e., in the L-axis direction in the illustrated embodiment. Similarly, the second non-electrode portion 22b is interposed between the second electrode portions 22a that generate capacitance in the multilayer ceramic capacitor 1 in the length direction of the cross section of the internal electrode layer, i.e., in the L-axis direction in the illustrated embodiment. In this specification, focusing on the arrangement of the first non-electrode portion 21b relative to the first electrode portion 21a and the arrangement of the second non-electrode portion 22b relative to the second electrode portion 22a, the first non-electrode portion 21b and / or the second non-electrode portion 22b may be referred to as "between internal electrodes" or "internal electrode regions".
[0037] 1-3 Ceramic layer 11 1-3-1 Composition of ceramic layer 11 The ceramic layer 11 contains a crystal of a ceramic material represented by the chemical formula ABO3 as a main component. That is, the ceramic layer 11 contains a crystal of an oxide represented by the chemical formula ABO3 as a main phase. This oxide may have a perovskite structure. A component contained in the ceramic layer 11 at 50 wt% or more based on the total mass of the ceramic layer 11 can be regarded as the main component of the ceramic layer 11. When the ceramic layer 11 contains an oxide represented by the chemical formula ABO3 at 50 wt% or more, it can be said that the ceramic layer 11 contains an oxide represented by the chemical formula ABO3 as a main component. The ceramic layer 11 preferably contains an oxide represented by the chemical formula ABO3 at 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.
[0038] In the chemical formula ABO3, "A" is at least one element selected from the group consisting of Ba (barium), Sr (strontium), Ca (calcium), and Mg (magnesium). In the chemical formula ABO3, "B" is at least one element selected from the group consisting of Ti (titanium), Zr (zirconium), and Hf (hafnium). When the oxide represented by the chemical formula ABO3 has a perovskite structure, the elements "A" and "B" are located at the A site and the B site of the perovskite structure, respectively. Examples of oxides contained as a main component in the ceramic layer 11 include BaTiO3 (barium titanate), CaZrO3 (calcium zirconate), CaTiO3 (calcium titanate), SrTiO3 (strontium titanate), and MgTiO3 (magnesium titanate).
[0039] The oxide contained as the main component in the ceramic layer 11 is represented by the chemical formula Ba 1-x-y Ca x Sr y Ti 1-z Zr zO3 (0≦x≦1, 0≦y≦1, 0≦z≦1). Examples of this type of oxide include barium strontium titanate, barium calcium titanate, barium zirconate, barium titanate zirconate, calcium titanate zirconate, and barium calcium titanate zirconate.
[0040] The ceramic layer 11 may contain an additive element in addition to the oxide of the main component. In one embodiment, the additive element contained in the ceramic layer 11 is at least one element selected from the group consisting of Fe, Ni, Mo, Nb (niobium), Ta (tantalum), W, Mg, Mn (manganese), V (vanadium), and Cr. The ceramic layer 11 may contain two or more types of the additive elements.
[0041] The ceramic layer 11 may contain an oxide of a rare earth element in addition to the oxide of the main component. The oxide of the rare earth element contained in the ceramic layer 11 may be an oxide of at least one rare earth element selected from the group consisting of Y (yttrium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), and Yb (ytterbium). The ceramic layer 11 may contain two or more types of oxides of rare earth elements.
[0042] The ceramic layer 11 may further include another type of oxide. For example, the ceramic layer 11 may include an oxide of at least one element selected from the group consisting of Co, Ni (nickel), Na (sodium), and K (potassium). The ceramic layer 11 may include two or more types of oxides of these elements.
[0043] In one embodiment, the thickness of the ceramic layer 11 (the dimension in the T-axis direction) is 0.2 to 10 μm.
[0044] 1-3-2 Crystal grains The ceramic layer 11 includes a plurality of crystal grains of a ceramic material. That is, the ceramic layer 11 is a polycrystalline body including a plurality of crystal grains 40. At least a portion of the plurality of crystal grains has a core-shell structure. With further reference to FIG. 4, the crystal grains included in the ceramic layer 11 will be described. FIG. 4 is an enlarged cross-sectional view showing an enlarged region A of the cross section of the main body 10 shown in FIG. 2, and FIG. 4 shows a schematic cross section of one crystal grain. Region A extends from the first internal electrode layer 21 through the ceramic layer 11 to the second internal electrode layer 22.
[0045] As shown in FIG. 3, the ceramic layer 11 includes a plurality of crystal grains 40 .
[0046] In the illustrated embodiment, the crystal grain 40 has a core portion 41 and a shell portion 42. An element (e.g., a rare earth element) added to the ceramic layer 11 is dissolved in a larger amount in the shell portion 42 than in the core portion 41. The core portion 41 and the shell portion 42 are distinguished, for example, by a contrast difference in a mapping image obtained by STEM-EDS. As described above, the added elements contained in the ceramic layer 11 are dissolved in a larger amount in the shell portion 42 than in the core portion 41, so that a region in the observation field where a large amount of these added elements are detected can be identified as the shell portion 42.
[0047] Adjacent crystal grains 40 are separated by grain boundaries 45. The crystal grains 40 have atoms regularly arranged, and grain boundaries 45 are interposed between adjacent ones of the crystal grains 40. The number of crystal grains 40 interposed between the first internal electrode layer 21 and the second internal electrode layer 22 adjacent to the first internal electrode layer 21 may be three or less, as shown in the figure. By reducing the number of crystal grains 40 interposed between the first internal electrode layer 21 and the second internal electrode layer 22, a high capacitance can be obtained. A first interface layer 47 is provided between the first internal electrode layer 21 and the crystal grains 40 adjacent to the first internal electrode layer 21. A second interface layer 48 is provided between the second internal electrode layer 22 and the crystal grains 40 adjacent to the second internal electrode layer 22.
[0048] In manufacturing the multilayer ceramic capacitor 1, a sintering aid is added to the ceramic green sheets, which are precursors of the ceramic layers 11, and a predetermined number of laminate units each having an internal electrode pattern containing a main component metal element such as Ni formed on the surface of the ceramic green sheets are laminated to form a green laminate, and the green laminate is fired to produce the multilayer ceramic capacitor 1. By firing the green laminate, the ceramic green sheets become the ceramic layers 11, and the internal electrode patterns become the first internal electrode layer 21 and the second internal electrode layer 22. During firing, the sintering aid becomes a liquid phase, and elements of the raw material powder contained in the ceramic green sheets are dissolved into the liquid phase, and the dissolved elements are precipitated on the crystals, thereby promoting the growth of the crystal grains 40. In addition, the rearrangement of the crystal grains 40 is promoted in the liquid phase, thereby densifying the ceramic layers 11. As the sintering aid, a low-melting glass can be used. The low-melting glass used as the sintering aid can contain, for example, SiO2, B2O3, and a mixture thereof. As the sintering aid, various low-melting glass can be used. Examples of low-melting glass that can be used as a sintering aid include borosilicate glass and phosphate glass. B2O3 or P2O5 powder or a mixture powder of these may be used as a sintering aid. In this specification, elements other than oxygen contained in the sintering aid may be called "sintering aid elements." For example, when a low-melting glass containing SiO2 is used as a sintering aid, Si is the sintering aid element. Examples of sintering aid elements include Si, B, and P.
[0049] By adding a sufficient amount of sintering aid to the ceramic green sheet, the sintering of the raw material powder contained in the ceramic green sheet is promoted, even when the sheet is fired at a low temperature (e.g., 1100°C or lower), and the densification of the crystal grains 40 is promoted.
[0050] The grain boundary 45, the first interface layer 47, and the second interface layer 48 contain a secondary phase formed by solidification of a sintering aid that became liquid during firing, and an oxide of an element contained in the main phase oxide (main component oxide) that constitutes the ceramic layer 11. For example, when the main component oxide of the ceramic layer 11 is barium titanate, the grain boundary 45, the first interface layer 47, and the second interface layer 48 contain a secondary phase, an oxide of titanium (TiO2), and an oxide of barium (BaO).
[0051] 1-4 Segregation area Segregation portions may be precipitated in the first non-electrode portion 21b and the second non-electrode portion 22b. In the example shown in Fig. 3, segregation portions 51a, 51b, 51c, 51d, 51e, 51f, and 51g are precipitated in the first non-electrode portion 21b, and segregation portions 52a, 52b, 52c, and 52d are precipitated in the second non-electrode portion 22b. The segregation portions 51a, 51b, 51c, 51d, 51e, 51f, and 51g and the segregation portions 52a, 52b, 52c, and 52d are all formed by solidifying a liquid-phase sintering aid that has flowed into the first non-electrode portion 21b or the second non-electrode portion 22b during the manufacturing process of the multilayer ceramic capacitor 1. In this specification, when there is no need to distinguish the segregated portions 51a, 51b, 51c, 51d, 51e, 51f, and 51g and the segregated portions 52a, 52b, 52c, and 52d from one another, they are collectively referred to as "segregated portions."
[0052] As described above, the first internal electrode layer 21 and the second internal electrode layer 22 (and the internal electrode patterns which are their precursors) contain a sub-element (e.g., Al) which easily forms a compound with the main component of the sintering aid added to the raw material of the ceramic layers 11, so that the liquid phase sintering aid easily flows into the first non-electrode portions 21b from the ceramic green sheets which are the precursors of the ceramic layers 11. For this reason, in the multilayer ceramic capacitor 1, segregation portions containing sintering aid elements which were not seen in conventional multilayer ceramic capacitors are precipitated in the first non-electrode portions 21b and the second non-electrode portions 22b.
[0053] As described above, the segregation portion is formed by solidifying the sintering aid in the liquid phase, and therefore contains the sintering aid element. In one embodiment, the concentration of the sintering aid element in the segregation portion is 20 at% or more. In this specification, unless otherwise specified or interpreted differently in the context, the concentration of the sintering aid element means the atomic ratio (at%) of the sintering aid element when the element (e.g., Ti element) that enters the B site of the main phase of the ceramic layer 11 in the observation area is 100 at%. Therefore, the concentration of the segregation portion is expressed by quantifying the B site element and the sintering aid element present in the segregation portion in the observation area including the segregation portion, and the atomic ratio of the sintering aid element to the quantified B site element 100 at%. For example, when barium titanate is used as the main component oxide of the ceramic layer 11 and a low-melting glass containing SiO2 is used as the sintering aid, the atomic ratio of the Si element to 100 at% of the Ti element contained in the segregation portion is the concentration of the sintering aid element in the segregation portion. The concentration of the segregated portion contained in the main body 10 may be determined by quantitating the concentrations at ten points in the segregated portion.
[0054] The segregation portion may contain the sub-element contained in the first internal electrode layer 21 and the second internal electrode layer 22. As described above, the first internal electrode layer 21 and the second internal electrode layer 22 contain an element that is likely to form a compound with the main component of the sintering aid as a sub-element, so that in the liquid phase that has flowed into the first non-electrode portion 21b and the second non-electrode portion 22b, the sub-element is dissolved from the first internal electrode layer 21 and the second internal electrode layer 22, and the sub-element dissolved in this liquid phase and the sintering aid element are likely to form a compound. Such a compound is, for example, 3Al2O3·2SiO2 or Zn2SiO4.
[0055] In one embodiment, the concentration of the sub-element in the segregation portion is 5 at% or more. In the segregation portion, the sub-element may be present in the form of a compound with a sintering aid element. The segregation portion may contain an oxide of the sub-element. The concentration of the sub-element in the segregation portion means the atomic ratio (at%) of the sub-element when the element (e.g., Ti element) that enters the B site of the main phase of the ceramic layer 11 is taken as 100 at%.
[0056] 3, the segregation portion is precipitated in all the first non-electrode portions 21b of the first internal electrode layer 21 and all the second non-electrode portions 22b of the second internal electrode layer 22, but the segregation portion may not be precipitated in some of the first non-electrode portions 21b and / or some of the second non-electrode portions 22b. The precipitation portion may be precipitated so as to block the entirety of a certain first non-electrode portion 21b or second non-electrode portion 22b, or may be precipitated so as to occupy only a part of it.
[0057] If the amount of precipitation in the segregation portion is large, the area of the portions of the first internal electrode layer 21 and the second internal electrode layer 22 that contribute to the generation of capacitance (i.e., the first electrode portion 21a and the second electrode portion 22a) is reduced, and the capacitance of the multilayer ceramic capacitor 1 is deteriorated. Therefore, in order to ensure the capacitance of the multilayer ceramic capacitor 1, it is desirable to set an upper limit for the amount of precipitation in the segregation portion. The amount of precipitation in the segregation portion can be expressed by polishing the multilayer ceramic capacitor 1 so that the LT surface becomes the observation surface, measuring the areas of the first internal electrode layer 21, the second internal electrode layer 22, and the segregation portion on this observation surface, and expressing the amount of precipitation in the segregation portion as a ratio of a second area representing the total area of the segregation portion to a first area representing the total area of the first internal electrode layer 21 and the second internal electrode layer 22. In other words, it can be considered that the larger the ratio of the second area to the first area (second area / first area), the larger the amount of precipitation in the segregation portion. In one embodiment, the ratio of the second area to the first area is 35% or less.
[0058] On the other hand, if the second area of the segregation portion is small despite the addition of a sintering aid to the ceramic green sheet, which is the precursor of the ceramic layer 11, it means that the sintering aid remains in the ceramic layer 11. Since the sintering aid element or its compound has a smaller relative dielectric constant than the main phase oxide (e.g., barium titanate) of the ceramic green sheet, when the second area of the segregation portion is small, the amount of sintering aid remaining in the ceramic layer 11 increases, resulting in a decrease in the capacitance of the multilayer ceramic capacitor. Therefore, it is desirable to set a lower limit for the amount of precipitation of the segregation portion. From this viewpoint, in one embodiment, the ratio of the second area to the first area is set to be 5% or more.
[0059] 1-5 First external electrode 31 and second external electrode 32 In one embodiment, the first external electrode 31 and the second external electrode 32 are formed by applying a conductive paste to the main body 10 and heating the conductive paste. The conductive paste may include at least one material selected from the group consisting of Ag, Pd, Au, Pt, Ni, Sn, Cu, W, Ti, and alloys thereof.
[0060] 2. Manufacturing method of multilayer ceramic capacitor 1 Next, an example of a method for manufacturing the multilayer ceramic capacitor 1 will be described with reference to Figures 5, 6a, and 6b. Figure 5 is a flow diagram showing the flow of a method for manufacturing a multilayer ceramic capacitor according to one embodiment of the present invention.
[0061] Briefly explaining the manufacturing method shown in FIG. 5, in step S1, a green laminate which is a precursor of the main body 10 is formed. This green laminate includes a ceramic green sheet which is a precursor of the ceramic layer 11, and an internal conductor pattern which is a precursor of each of the first internal electrode layer 21 and the second internal electrode layer 22. The internal conductor pattern contains a main component metal element such as Ni. The green laminate may be formed by alternately laminating a ceramic green sheet on which an internal conductor pattern which is a precursor of the first internal electrode layer 21 is provided on the surface and a ceramic green sheet on which an internal conductor pattern which is a precursor of the second internal electrode layer 22 is provided on the surface. The ceramic green sheet contains a sintering aid. The internal conductor pattern contains sub-elements such as Al, Zn, B, and Si in addition to the main component metal element. The internal conductor pattern may contain elements other than those mentioned above, for example, a third element such as Au or Fe. Next, in step S2, the green laminate formed in step S1 is placed in a sintering furnace, and the temperature of the sintering furnace is raised to a keep temperature that is higher than the softening point of the sintering aid and at which the sintering of the main component metal elements in the internal electrode pattern progresses, and the green laminate is heated at this keep temperature for a first holding time. Next, in step S3, the temperature in the sintering furnace is raised to the sintering top temperature to sinter the ceramic material in the ceramic green sheet. Finally, in step S4, the inside of the sintering furnace is cooled to obtain the multilayer ceramic capacitor 1.
[0062] Each step shown in FIG. 5 will be described in more detail below. First, in step S1, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, a plasticizer, and a sintering aid are added to the ceramic powder and wet mixed to obtain a slurry. As the sintering aid, for example, low-melting glass containing SiO2, B2O3, and a mixture thereof can be used. Examples of low-melting glass include borosilicate glass and phosphate glass. B2O3 powder or P2O5 powder may be used as the sintering aid. Then, this slurry is applied onto a substrate film by, for example, a die coater method or a doctor blade method, and the slurry applied onto the substrate film is dried to obtain a ceramic green sheet. The ceramic green sheet is a precursor of the ceramic layer 11.
[0063] The ceramic powder, which is the raw material powder of the ceramic green sheet, is, for example, barium titanate powder. The barium titanate powder is synthesized by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate by a known method such as a solid-phase method, a sol-gel method, or a hydrothermal method.
[0064] Next, the internal electrode patterns are formed on the plurality of ceramic green sheets formed as described above. The internal electrode patterns are formed, for example, by printing the internal electrode paste on the ceramic green sheets by a known printing method such as screen printing. When the internal electrode patterns are formed by screen printing, the internal electrode paste is manufactured by kneading metal powder, binder resin, and solvent with a three-roll mill. That is, the internal electrode paste is a paste in which metal powder is dispersed in binder resin. The metal powder contained in the internal electrode paste may be a mixed powder obtained by mixing powder of a main component metal element such as Ni, Cu, Sn, etc., which is the main component of the first internal electrode layer 21 and the second internal electrode layer 22, with powder containing a sub-element. Powder of a third element such as Au, Fe, etc. may also be added to this mixed powder. The mixed powder is generated by mixing the main component metal powder with the sub-element powder so that the content ratio of the sub-element to 100 at% of the main component metal element is in the range of 0.01 to 5 at%. As the organic binder for the internal electrode paste, a cellulose-based resin such as ethyl cellulose or an acrylic resin such as butyl methacrylate can be used. The internal electrode pattern formed on some of the ceramic green sheets is a precursor of the first internal electrode layer 21, and the internal electrode pattern formed on the other ceramic green sheets is a precursor of the second internal electrode layer 22.
[0065] The internal electrode pattern may be formed on the ceramic green sheet by a sputtering method. The method of forming the internal electrode pattern is not limited to the method specifically described in this specification. The internal electrode pattern may be formed by various known methods, such as vacuum deposition, PLD (pulsed laser deposition), MO-CVD (metal organic chemical vapor deposition), MOD (metal organic decomposition), or CSD (chemical solution deposition).
[0066] In this manner, a laminate unit having a ceramic green sheet and an internal electrode pattern formed on the surface of the ceramic green sheet is obtained. A predetermined number of such laminate units are laminated and thermocompression bonded to obtain a green laminate. Green sheets without an internal electrode pattern may be laminated on the top and bottom layers of the green laminate.
[0067] Next, the green laminate is singulated to obtain a chip-shaped green laminate that serves as a precursor of the main body 10. The chip-shaped green laminate may be subjected to a degreasing treatment. The degreasing treatment may be performed in an N2 atmosphere. Furthermore, a metal paste that serves as the base electrode layers of the first external electrode 31 and the second external electrode 32 may be applied by a dipping method to the green laminate that has been subjected to the degreasing treatment.
[0068] FIG. 6a is a schematic enlarged view of a cross section of a chip-shaped green laminate cut along the lamination direction. As shown in FIG. 6a, in the green laminate 110, an internal electrode pattern 121, which is a precursor of the first internal electrode layer 21, is provided on one surface in the lamination direction of a ceramic green sheet 111, and an internal electrode pattern 122, which is a precursor of the second internal electrode layer 22, is provided on the other surface in the lamination direction of the ceramic green sheet 111. The ceramic green sheet 111 contains a ceramic powder 61 and a sintering aid powder 62. The ceramic powder 61 is, for example, a barium titanate powder. The sintering aid powder 62 is, for example, a low-melting-point glass powder containing SiO2. The internal electrode patterns 121 and 122 contain a main component metal element powder 71 and a sub-element powder 72. The main component metal element powder 71 is, for example, a Ni powder. The sub-element powder 72 is, for example, an Al powder.
[0069] Next, the chip-shaped green laminate 110 produced in step S1 is placed in a firing furnace, and the green laminate 110 is fired in the firing furnace according to a predetermined temperature profile. Through this firing process, the ceramic green sheets 111 in the green laminate 110 are fired to become the ceramic layers 11, the internal electrode patterns 121 are fired to become the first internal electrode layers 21, and the internal electrode patterns 122 are fired to become the second internal electrode layers 22.
[0070] In the firing process, first, the temperature in the firing furnace is raised from room temperature to an intermediate temperature at a rate of 200 to 300°C / h. The intermediate temperature is set to a temperature slightly lower than the sintering temperature of the main component metal element. When the main component metal element is Ni, the intermediate temperature is set to about 500 to 700°C. An example of the intermediate temperature is 600°C.
[0071] Next, in step S2, the temperature of the sintering furnace is raised from the intermediate temperature to a keep temperature. The temperature in the sintering furnace is kept at the keep temperature for a first hold time. That is, in step S2, the green laminate is heated at the keep temperature for a first hold time (first heating step). The keep temperature is higher than the softening point of the sintering aid, and is a temperature at which the sintering of the main component metal element in the internal electrode pattern progresses. The keep temperature can vary depending on the type of sintering aid and the type of main component metal element. When a low-melting point glass mainly composed of SiO2 is used as the sintering aid and Ni is used as the main component metal element, the keep temperature can be set to 1000°C. By maintaining the green laminate at the keep temperature, the sintering aid softens and becomes liquid, and sintering of the main component metal element begins in the internal electrode pattern. In this step S2, a part of the main component metal element becomes spherical as the sintering progresses, and a part of the internal electrode pattern becomes discontinuous. The portions where the internal electrode pattern is discontinuous become the first non-electrode portion 21b and the second non-electrode portion 22b in the completed multilayer ceramic capacitor 1. In step S2, the liquid phase sintering aid flows into the discontinuous portions of the internal electrode pattern. The first holding time is set to a time sufficient for the liquid phase sintering aid to flow into the discontinuous portions of the internal electrode pattern, and is set to, for example, between 10 minutes and 60 minutes. The first holding time is, for example, 30 minutes.
[0072] In the first heating step of step S2, the sub-elements contained in the internal electrode pattern move to the surface of the internal electrode pattern by thermal diffusion and dissolve into the liquid phase sintering aid flowing into the discontinuous portion of the internal electrode pattern. In the liquid phase sintering aid, the main component of the sintering aid and the sub-elements dissolved in the sintering aid form a compound.
[0073] After heating for the first holding time in step S2, the temperature in the firing furnace is raised to the top firing temperature in step S3. The temperature in the firing furnace is held at the top firing temperature for the second holding time. That is, in step S3, the green laminate is heated at the top firing temperature for the second holding time (second heating step). The top firing temperature is, for example, 1100 to 1200°C. The second holding time at the top firing temperature is set to within 10 minutes to prevent excessive sintering of the main component metal elements in the internal electrode layers. Cooling may be started immediately after the top firing temperature is reached.
[0074] In the second heating step, the green laminate 110 is heated to the top firing temperature, and the green laminate 110 is fired to become the main body 10. Fig. 6b is an enlarged schematic cross-sectional view of the main body 10 obtained by heating the green laminate 110 to the top firing temperature and holding the main body 10 at the top firing temperature for a second holding time. Fig. 6b shows the main body 10 before it is cooled after being heated to the top firing temperature.
[0075] In the main body 10 shown in FIG. 6b, the ceramic powder 61 in the green laminate 110 is sintered by the firing process in step S2 to form crystal grains 40 having a core portion 41 and a shell portion 42. If the ceramic powder 61 contains an additive element such as a rare earth element, the additive element diffuses to the shell portion 42 during the firing process. Therefore, the additive element in the ceramic powder 61 is contained in a higher concentration in the shell portion 42 than in the core portion 41. In the ceramic layer 11, the crystal grains 40 are densely arranged. Adjacent crystal grains 40 are separated by grain boundaries 45. During the firing process, the sintering aid powder 62 in the ceramic green sheet 111 exists as a liquid phase component 80 of the liquid phase.
[0076] The liquid phase component 80 formed by melting the sintering aid powder in the second heating step spreads over the surface of the ceramic powder 61, promoting the sintering of the ceramic powder 61. In the main body 10, the liquid phase component 80 spreads over the surface of the crystal grains formed by sintering the ceramic powder 61, so that the grain boundaries 45 of the main body 10 are filled with the liquid phase component 80, as shown in FIG. 6b. Elements contained in the ceramic powder 61 (Ba and Ti in the case where the ceramic powder is barium titanate powder) are dissolved in the liquid phase component 80. In the firing step, the elements dissolved in the liquid phase component 80 are precipitated on the crystal surface, and thus the growth of the crystal grains 40 progresses. In addition, the rearrangement of the crystal grains 40 progresses in the liquid phase component 80, and thus the densification of the crystal grains 40 progresses.
[0077] The liquid phase component 80 spreads from the grain boundary 45 through the first interface layer 47 to between the internal electrodes (in the first non-electrode portion 21b of the first internal electrode layer 21 in the illustrated example). The first non-electrode portion 21b may be entirely filled with the liquid phase component 80, or only a part of the first non-electrode portion 21b may be filled with the liquid phase component 80. When the second non-electrode portion 22b is formed in the second internal electrode layer 22, the liquid phase component 80 may spread to the second non-electrode portion 22b through the second interface layer 48. Since the first internal electrode layer 21 and the second internal electrode layer 22 contain a subelement that is likely to form a compound with the sintering aid element contained in the liquid phase component, the liquid phase component 80 does not remain in the grain boundary 45, the first interface layer 47, and the second interface layer 48, but moves toward the first non-electrode portion 21b and the second non-electrode portion 22b.
[0078] In the second heating step in step S3, the sintering of the main component metal elements in the internal electrode patterns 121 and 122 also progresses further. A part of the main component metal elements becomes spherical as the sintering progresses, and the first internal electrode layer 21 and the second internal electrode layer 22 become partially discontinuous. FIG. 6b shows the first non-electrode portion 21b formed by the progress of the sphericalization of a part of the main component metal elements of the first internal electrode layer 21. As the sintering of the main component metal elements progresses, the sintered body of the main component metal elements grows so as to be curved convexly toward the first non-electrode portion 21b. At this time, the liquid phase component 80 filled in the first non-electrode portion 21b has high fluidity, so it flows within the main body 10 according to the growth of the sintered body of the main component metal elements. In this way, since the first non-electrode portion 21b is filled with the liquid phase component 80 in the second heating step, the main component metal elements of the first internal electrode layer 21 can grow so as to have a curved surface convexly toward the first non-electrode portion 21b.
[0079] FIG. 7 shows an enlarged cross-sectional view of a conventional multilayer ceramic capacitor 301. The conventional multilayer ceramic capacitor 301 has a first internal electrode layer 321, a second internal electrode layer 322, and a ceramic layer 311 disposed therebetween. In FIG. 7, for the sake of simplicity, the illustration of crystal grains contained in the ceramic layer 311 is omitted. The first internal electrode layer 321 has an electrode portion 321a and a non-electrode portion 321b. In the conventional multilayer ceramic capacitor 301, liquid phase components do not flow into the non-electrode portion 321b during the manufacturing process, so that when sintering of the main component metal element progresses, the non-electrode portion 321b initially exists as a void. Then, when the firing temperature is further increased and sintering of the ceramic particles progresses, a sintered body of the ceramic particles also grows in the non-electrode portion 321b, which is a void. For this reason, as shown in FIG. 7, the non-electrode portion 321b is filled with a sintered body of ceramic particles with low fluidity like the ceramic layer 311, so the sintered body of the main component metal element cannot have a convex shape toward the non-electrode portion 321b. For this reason, as shown in FIG. 7, the interface between the electrode portion 321a and the non-electrode portion 321b has a flat shape. For this reason, when a voltage is applied between the first internal electrode layer 321 and the second internal electrode layer 322, an electric field is likely to concentrate at the apex P1 where the interface between the electrode portion 321a and the non-electrode portion 321b and the interface between the electrode portion 321a and the ceramic layer 311 intersect. This concentration of the electric field causes a decrease in the life of the multilayer ceramic capacitor.
[0080] In contrast, in the multilayer ceramic capacitor 1 according to the embodiment of the present invention, as shown in Fig. 4 and Fig. 6b, when the main component metal element is sintered, the first non-electrode portion 21b is filled with a highly fluid liquid phase component 80, so that the sintered body of the main component metal element can grow so as to be curved convexly toward the first non-electrode portion 21b. Therefore, the interface between the first electrode portion 21a and the first non-electrode portion 21b has a shape that is curved convexly toward the first non-electrode portion 21b. Therefore, in the multilayer ceramic capacitor 1 according to the embodiment of the present invention, the concentration of the electric field that occurs in the conventional multilayer ceramic capacitor shown in Fig. 7 is alleviated, and a multilayer ceramic capacitor 1 having a longer life can be obtained.
[0081] After the laminate is held at the keep temperature for a second holding time in step S3, the firing furnace is cooled to room temperature in step S4 to obtain the multilayer ceramic capacitor 1. By cooling in step S4, the liquid phase component 80 in the main body 10 is solidified to form a secondary phase. The secondary phase contains a sintering aid element. Furthermore, by cooling the liquid phase component 80, the elements of the main phase components (e.g., Ba and Ti) that have dissolved in the liquid phase component 80 are precipitated as oxides (BaO and TiO2) between the internal electrodes, in the first interface layer 47, the second interface layer 48, and in the grain boundaries 45.
[0082] 5 may be performed to manufacture the multilayer ceramic capacitor 1. For example, the multilayer ceramic capacitor 1 obtained by the second heating treatment in step S3 may be subjected to a reoxidation treatment at 600°C to 1000°C in an N2 gas atmosphere. Furthermore, a plating layer of Cu, Ni, Sn, or the like may be provided on the surfaces of the first external electrode 31 and the second external electrode 32. This plating layer may be formed by electrolytic plating or electroless plating.
[0083] In order to manufacture the multilayer ceramic capacitor 1, some of the steps shown in the flow diagram of FIG. 5 can be omitted. For example, the first heating step in step S2 can be omitted. When the first heating step is omitted, the temperature is raised from the intermediate temperature to the firing top temperature at a predetermined heating rate. Even if the first heating step in step S2 is omitted, the liquid phase component 80 can be discharged to the first non-electrode portion 21b and the second non-electrode portion 22b by making the internal electrode pattern, which is the precursor of the first internal electrode layer 21 and the second internal electrode layer 22, contain a sub-element that easily forms a compound with the sintering aid element. However, when the internal electrode pattern does not contain such a sub-element, the first heating step is performed to advance the sintering of the main component metal element contained in the internal electrode pattern and to wet and spread the liquid phase sintering aid to the discontinuous portion of the internal electrode pattern.
[0084] 3. Working Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0085] 3-1 Sample preparation First, 17 kinds of samples were prepared as follows according to the manufacturing method described in FIG. 5. Specifically, first, polyvinyl butyral (PVB) resin, a solvent, a plasticizer, and a sintering aid powder were added to barium titanate powder and wet mixed to obtain a slurry. The sintering aid powder was weighed so that the content ratio of the main component (sintering aid element) of the sintering aid powder to Ti100 at% was the amount described in "Sintering aid addition amount" in Table 1, and this weighed auxiliary element powder was mixed with barium titanate powder. For example, when preparing sample 1, a low-melting point glass powder mainly composed of SiO2 was weighed so that Si was 0.1 at% relative to Ti100 at% contained in the barium titanate powder, and this weighed low-melting point glass powder mainly composed of SiO2 was mixed with barium titanate powder. When preparing sample 9, barium titanate powder was mixed with B2O3 powder. Sample 10 was prepared by mixing barium titanate powder with P2O5 powder.
[0086] The slurry thus formed was applied onto a substrate film, and the applied slurry onto the substrate film was dried to obtain a ceramic green sheet. Next, Ni powder, which is the main component metal element, was mixed with a sub-element powder containing the sub-elements listed in Table 1 to prepare a mixed powder. However, when preparing samples 12 and 13, the sub-elements were not mixed. The sub-element powder was weighed so that the content ratio of the sub-element relative to Ni 100 at% was the amount listed in "Sub-element Addition Amount" in Table 1, and this weighed sub-element powder was mixed with Ni powder. Next, polyvinyl butyral (PVB) resin, a solvent, and a plasticizer were added to this mixed powder and wet-mixed to obtain a slurry for an internal electrode. Then, the slurry for an internal electrode was printed on a partial area of the surface of the ceramic green sheet to form an internal electrode pattern on each of the ceramic green sheets, thereby forming a laminate unit. This laminate unit has a ceramic green sheet and an internal electrode pattern formed on the surface of the ceramic green sheet.
[0087] [Table 1]
[0088] Next, 500 laminated units were laminated to form a laminate, and this laminate was divided into individual pieces to obtain a chip-shaped green laminate (chip laminate). The chip laminate had a 1005 shape (length: 1.0 mm, width: 0.5 mm, height: 0.5 mm). Next, this chip laminate was degreased in an N2 atmosphere. Next, a metal paste was applied to the molded body after the degreased process by a dipping method to form an underlayer for an external electrode on each chip laminate.
[0089] Next, the chip stacks, which are precursors of each sample obtained as described above, were placed in a sintering furnace, and the chip stacks were sintered under predetermined sintering conditions according to a predetermined temperature profile. During sintering of Samples 1 to 11, Samples 13 to 15, and Sample 17, the inside of the sintering furnace was kept at an oxygen partial pressure of 10 -10The furnace was kept in a low-oxygen atmosphere at 200 MPa, and the temperature inside the furnace was raised from room temperature to 600°C at a rate of 300°C / h, then raised from 600°C to 1200°C at a rate of 1000°C / h, and the top firing temperature of 1200°C was held for 5 minutes (second holding time). When firing Sample 12, the temperature inside the firing furnace was raised from the intermediate temperature to 1000°C (keep temperature), the chip stack was heated at this keep temperature for 30 minutes (first hold time), and after the first hold time had elapsed, the temperature inside the firing furnace was raised to the top firing temperature of 1200°C. After being held at the top firing temperature for 5 minutes, the inside of the firing furnace was cooled.
[0090] In this manner, samples of multilayer ceramic capacitors, Samples 1 to 17, were produced. In Samples 1 to 17, the ceramic green sheets were fired to form ceramic layers, and the internal electrode patterns were fired to form internal electrode layers.
[0091] Each of the samples 1 to 17 was embedded in resin, and each sample embedded in resin was polished along a plane parallel to the lamination direction (for example, the LT plane in FIG. 2) to expose a cross section parallel to the lamination direction, and the exposed cross section was observed at a magnification of 20,000 times with a field emission scanning secondary electron microscope (FE-SEM). From this observation, it was confirmed that the crystal grains were densified in all of the samples 1 to 16. Thus, the samples 1 to 16 were sintered at a low densification temperature of 1200°C. The crystal grains in the sample 17 were not densified.
[0092] 3-2 Identification of segregated areas and their area ratios Next, for each of Samples 1 to 16, the observation surface exposed by polishing was observed by a field emission scanning secondary electron microscope (FE-SEM) equipped with an energy dispersive X-ray spectrometer (EDS), and the area that appeared bright due to contrast difference in the SEM image was identified as the electrode part of the internal electrode layer (the first electrode part 21a or the second electrode part 22a). In addition, on the above observation surface, an observation area was set to a size of 50 μm square so that five internal electrode layers were included, and EDS mapping was performed in this observation area to examine the distribution of Ni, Ba, Ti, sintering aid elements, and auxiliary elements. As the field emission scanning secondary electron microscope, a FE-SEM (SU7000) manufactured by Hitachi High-Technologies Corporation was used. As the EDS detector, a Quantax manufactured by BRUKER Corporation was used.
[0093] In the mapping data thus obtained, the region between the internal electrodes where the concentration of the sintering aid element was 20 at% or more was identified as the segregation portion. In addition, the region where the concentration of the Ni element was the highest among the quantitative elements was identified as the first electrode portion 21a or the second electrode portion 22a. Next, the mapping data was subjected to image processing using the image processing software ImageJ to calculate the first area representing the sum of the area of the first internal electrode layer 21 and the area of the second internal electrode layer 22, and the second area representing the area of the segregation portion, and the ratio of the second area to the first area was calculated. The ratio of the second area to the first area thus calculated is listed in the "area ratio" column of Table 2 below.
[0094] 3-3 Continuity rate In addition, the continuity ratio of the internal electrode layer in each sample was calculated as follows. For each of the internal electrode layers included in each of the above observation regions, the electrode portion (first electrode portion 21a or second electrode portion 22a) was identified based on the contrast difference, and the length of each of these electrode portions at the center in the thickness direction (T-axis direction) was measured. Then, based on the measured length of each electrode portion, the continuity ratio for each internal electrode layer was calculated. The continuity ratio of the internal electrode layer calculated in this manner is listed in the "continuity ratio" column of Table 2. The segregation portion may occupy only a part of each of the first non-electrode portions 21b rather than the entirety, and similarly, may occupy only a part of each of the second non-electrode portions 22b rather than the entirety, so even if the continuity ratio increases, the area ratio does not necessarily increase immediately.
[0095] 3-4 Capacitance The capacitance was measured for each of Samples 1 to 16. The capacitance was measured using an LCR meter under the conditions of room temperature, measurement voltage of 0.5 V, and frequency of 1 kHz after each sample was left at 150°C for 1 hour and then left at standard conditions for 24 hours. 100 samples were selected for each of Samples 1 to 16, and the capacitance was determined for each of the 100 samples. The average value of the capacitance measured for the 100 samples for each sample was calculated, and this calculated average value was used as the capacitance of the sample. The capacitance calculated in this manner is listed in the "Initial Capacitance" column of Table 2.
[0096] 3-5 HALT For each of samples 1 to 16, 100 samples were selected, and an accelerated life test (HALT) was performed on each of the selected samples. In the accelerated life test, a voltage of 6.3 V / μm was applied at 85° C. for 1000 hours to each of the 100 samples selected for each of samples 1 to 16. A voltage was applied for 2000 hours under the same conditions to each of the other 100 samples selected for each of samples 1 to 16. For these samples, the samples were left at room temperature for 24 hours after the voltage application, and then the insulation resistance was measured. In this measurement, samples with an insulation resistance value of less than 10 MΩ were judged to have failed. For samples in which no failure occurred even after 2000 hours of voltage application, the life was judged to be very good, and a “◎” was entered in the “Life” column of Table 2. For samples in which no failure occurred even after 1000 hours of voltage application, but a sample that failed after 2000 hours of voltage application was found, the life was judged to be good, and a “○” was entered in the “Life” column of Table 2.
[0097] [Table 2]
[0098] In Table 2, samples not included in the present invention (i.e., comparative examples) are marked with an asterisk (*) next to the sample number. Specifically, samples 13 to 17 are comparative examples not included in the present invention. In sample 17, a densified ceramic layer was not obtained at the top firing temperature of 1200°C, so the area ratio, continuity rate, initial capacity, and life were not evaluated.
[0099] From the above experimental results, it was confirmed that the capacitance of Samples 1 to 12 in which segregation parts were precipitated between the internal electrodes was 21 μF to 22 μF, and therefore Samples 1 to 12 all had superior capacitance compared to Samples 13 and 16 in which segregation parts were not precipitated (capacity: 15 μF). In Sample 13, since the internal electrode pattern, which is the precursor of the internal electrode layer, does not contain auxiliary elements, and the process of holding at a keep temperature (first heating process) is not performed in the manufacturing process, most of the sintering aid contained in the ceramic green sheet remains in the ceramic layer 11, and therefore the capacitance is considered to be low. On the other hand, in Samples 1 to 11, since the auxiliary elements that easily form compounds with the sintering aid elements are added to the internal electrode pattern at a rate of 0.1 at% to 10 at%, it is considered that the sintering aid in the liquid phase flows between the internal electrodes during the process of preparing the samples, and the content of the sintering aid elements with low dielectric constant in the ceramic layer 11 decreases, thereby improving the capacitance. In sample 12, no auxiliary elements were added to the internal electrode pattern, but a process of maintaining the temperature at a keep temperature (first heating step) was performed during the manufacturing process. It is believed that in this first heating step, the liquid phase sintering aid flowed between the internal electrodes, resulting in an improvement in capacitance.
[0100] A good life was obtained in all of the samples 1 to 12. On the other hand, in the samples 13 and 16 in which no segregation was precipitated, the life was reduced compared to the samples 1 to 12. In the samples 13 and 16, the liquid phase sintering aid did not flow between the internal electrodes during the manufacturing process, so that a peak was formed in a part of the internal electrode layer as shown in FIG. 7, and the electric field was concentrated at this peak, which is considered to have reduced the life. On the other hand, in the samples 1 to 12, the precipitation of the segregation between the internal electrodes was confirmed, so that it is considered that the liquid phase component flowed between the internal electrodes during the manufacturing process. Therefore, in the samples 1 to 12, the interface between the electrode portion (for example, the first electrode portion 21a) and the non-electrode portion (for example, the first non-electrode portion 21b) is curved, and the concentration of the electric field in the internal electrode layer is considered to have been alleviated. In other words, it is considered that the concentration of the electric field was alleviated in the samples 1 to 12, so that a good life was obtained.
[0101] In Sample 14, the internal electrode pattern contains a high content (10 at%) of Al as a secondary element, while the amount of sintering aid elements added to Ti (100 at%) is about 1 at%, so solid phase Al2O3 precipitated in the non-electrode parts, and it is believed that this solid phase Al2O3 reduced the continuity rate.
[0102] In sample 15, the amount of sintering aid added was large, and a large amount of the secondary element (Al) of 12 at% was added to the internal electrode pattern, so the sintering aid flowed into the gaps between the internal electrodes, causing excessive sintering of the Ni element in the internal electrode pattern, which is thought to have resulted in a decrease in the continuity rate. This decrease in the continuity rate also causes a decrease in the capacitance.
[0103] As described above, in Samples 14 and 15, which have an area ratio of 38 or more, the capacitance is reduced to 15 to 17 μF. Thus, it is found that excessive precipitation in the segregation area leads to a reduction in capacitance. It is considered that excellent capacitance can be obtained by adjusting the amount of precipitation in the segregation area so that the area ratio is 35% or less.
[0104] Although the description of the experimental results is omitted, it was observed that even when B or P was used as the sintering aid element instead of Si, a decrease in capacitance occurred when the area ratio exceeded 35%. By precipitating the segregation portion between the internal electrodes, the amount of sintering aid contained in the ceramic layer 11 can be reduced, and therefore the capacitance can be increased. However, under conditions where the area ratio is 35% or more, the segregation portion is excessively precipitated, and as a result, the continuity rate of the internal electrode layer is reduced, causing a decrease in the capacitance. For this reason, it is desirable to precipitate the segregation portion between the internal electrodes so that the area ratio is 35% or less.
[0105] 4 Notes The dimensions, materials, and arrangements of each component described in the various embodiments above are not limited to those explicitly described in each embodiment, and each component can be modified to have any dimensions, materials, and arrangements that may fall within the scope of the present invention.
[0106] Components not explicitly described in this specification may be added to each of the above-described embodiments, and some of the components described in each embodiment may be omitted.
[0107] The designations "first," "second," "third," and the like in this specification are given to identify components, and do not necessarily limit the number, order, or content. Furthermore, numbers for identifying components are used in different contexts, and a number used in one context does not necessarily indicate the same configuration in another context. Furthermore, a component identified by a certain number does not prevent the component from also having the function of a component identified by another number.
[0108] In this specification, when a certain component is referred to as "comprising," it does not mean that other components are excluded, but rather that other components may be further included, unless this is inconsistent with the content of the present invention.
[0109] 5. Supplementary Notes The embodiments disclosed herein also include the following. [Appendix 1] A main body having a first internal electrode layer containing a main component metal element, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer in a lamination direction and formed from a ceramic material to which a sintering aid containing a sintering aid element as a main component is added; a first external electrode provided on the body so as to be electrically connected to the first internal electrode layer; a second external electrode provided on the main body so as to be electrically connected to the second internal electrode layer; Equipped with The first internal electrode layer has a first electrode portion which is a sintered body of a main component metal element, and a first non-electrode portion surrounded by the first electrode portion, the second internal electrode layer has a second electrode portion which is a sintered body of a main component metal element, and a second non-electrode portion which is surrounded by the second electrode portion, the first non-electrode portion and the second non-electrode portion each have a segregation portion containing the sintering aid element, a ratio of a second area representing an area of the segregation portion to a first area representing a sum of an area of the first internal electrode layer and an area of the second internal electrode layer in a cross section obtained by cutting the main body along the stacking direction is 35% or less; Multilayer ceramic capacitor. [Appendix 2] The ratio of the second area to the first area is 5% or more. 2. The multilayer ceramic capacitor according to claim 1. [Appendix 3] The concentration of the sintering aid element in the segregation portion is 20 at% or more. 10. The multilayer ceramic capacitor according to claim 1 or 2. [Appendix 4] The first internal electrode layer further contains a subelement, The secondary element is at least one element selected from the group consisting of Al, Zn, B, and Si; 4. The multilayer ceramic capacitor according to claim 1, [Appendix 5] The segregation portion contains the subelement. 5. The multilayer ceramic capacitor according to claim 4. [Appendix 6] The concentration of the subelement in the segregation portion is 5 at% or more. 6. The multilayer ceramic capacitor according to claim 5. [Appendix 7] the ceramic layer includes a plurality of crystal grains that are a sintered body of the ceramic material; In the ceramic layers, the number of the crystal grains interposed between the first internal electrode layers and the second internal electrode layers is 3 or less. 7. The multilayer ceramic capacitor according to claim 1, [Appendix 8] A circuit module comprising the multilayer ceramic capacitor according to any one of claims 1 to 7. [Appendix 9] 9. An electronic device comprising the circuit module according to claim 8. [Appendix 10] a preparation step of preparing a green laminate including a ceramic green sheet containing a sintering aid and an internal electrode pattern provided on a first surface and a second surface of the ceramic green sheet and containing a main component metal element; a first heating step of heating the green laminate for a first holding time at a holding temperature higher than the softening point of the sintering aid and at which the main component metal element is sintered; a second heating step of heating the green laminate at a top firing temperature higher than the keep temperature after the first heating step; The method for manufacturing a multilayer ceramic capacitor includes the steps of: [Appendix 11] The internal electrode pattern contains a sub-element (wherein the sub-element is at least one element selected from the group consisting of Al, Zn, B, and Si). The manufacturing method described in Appendix 1. [Explanation of symbols]
[0110] 1. Multilayer ceramic capacitors 10 Main unit 11 Ceramic layer 21 1st internal electrode layer 22 Second internal electrode layer 21a 1st electrode part 21b First non-electrode part 22a 2nd electrode part 22b Second non-electrode part 31 1st external electrode 32 2nd external electrode 40 Grains 45 Grain boundaries 47 First interface layer 48 Second interface layer 51a, 51b, 51c, 51d, 51e, 51f, 51g, 52a, 52b, 52c, 52d Segregation part 80 Liquid phase composition
Claims
1. A main body having a first internal electrode layer containing a main component metal element, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer in a lamination direction and formed from a ceramic material to which a sintering aid containing a sintering aid element as a main component is added; a first external electrode provided on the main body so as to be electrically connected to the first internal electrode layer; a second external electrode provided on the main body so as to be electrically connected to the second internal electrode layer; Equipped with the first internal electrode layer has a first electrode portion which is a sintered body of a main component metal element, and a first non-electrode portion which is surrounded by the first electrode portion, the second internal electrode layer has a second electrode portion which is a sintered body of a main component metal element, and a second non-electrode portion which is surrounded by the second electrode portion, the first non-electrode portion and the second non-electrode portion each have a segregation portion containing the sintering aid element, a ratio of a second area representing an area of the segregation portion to a first area representing a sum of an area of the first internal electrode layer and an area of the second internal electrode layer in a cross section obtained by cutting the main body along the stacking direction is 35% or less; Multilayer ceramic capacitor.
2. a ratio of the second area to the first area is 5% or more; The multilayer ceramic capacitor according to claim 1 .
3. The concentration of the sintering aid element in the segregation portion is 20 at% or more.
3. The multilayer ceramic capacitor according to claim 1 or 2.
4. The first internal electrode layer further contains a subelement, The secondary element is at least one element selected from the group consisting of Al, Zn, B, and Si; 3. The multilayer ceramic capacitor according to claim 1 or 2.
5. The segregation portion contains the subelement. The multilayer ceramic capacitor according to claim 4.
6. The concentration of the sub-element in the segregation portion is 5 at% or more. The multilayer ceramic capacitor according to claim 5 .
7. the ceramic layer includes a plurality of crystal grains that are a sintered body of the ceramic material; In the ceramic layers, the number of the crystal grains interposed between the first internal electrode layers and the second internal electrode layers is 3 or less.
3. The multilayer ceramic capacitor according to claim 1 or 2.
8. A circuit module comprising the multilayer ceramic capacitor according to claim 1 .
9. An electronic device comprising the circuit module according to claim 8 .
10. a preparation step of preparing a green laminate including a ceramic green sheet containing a sintering aid and an internal electrode pattern provided on a first surface and a second surface of the ceramic green sheet and containing a main component metal element; a first heating step of heating the green laminate for a first holding time at a holding temperature higher than the softening point of the sintering aid and at which sintering of the main component metal element occurs; a second heating step of heating the green laminate at a top firing temperature higher than the keep temperature after the first heating step; The method for manufacturing a multilayer ceramic capacitor includes the steps of:
11. The internal electrode pattern contains a sub-element (wherein the sub-element is at least one element selected from the group consisting of Al, Zn, B, and Si). The method of claim 10.
Citation Information
Patent Citations
Dielectric ceramic composition, and laminated type electronic component
JP2009084111A